An intensified dosing schedule of subcutaneous methotrexate in patients with moderate to severe plaque-type psoriasis (METOP): a 52 week, multicentre, randomised, double-blind, placebo-controlled, phase 3 trial. Issue 10068 (4th February 2017) - Warren, Richard B; Mrowietz, Ulrich; von Kiedrowski, Ralph; Niesmann, Johannes; Wilsmann-Theis, Dagmar; Ghoreschi, Kamran; Zschocke, Ina; Falk, Thomas M; Blödorn-Schlicht, Norbert; Reich, Kristian
Summary: Background: Methotrexate is one of the most commonly used systemic drugs for the treatment of moderate to severe psoriasis; however, high-quality evidence for its use is sparse and limited to use of oral dosing. We aimed to assess the effect of an intensified dosing schedule of subcutaneous methotrexate in patients with moderate to severe plaque-type psoriasis. Methods: We did this prospective, multicentre, randomised, double-blind, placebo-controlled, phase 3 trial (METOP) at 16 sites in Germany, France, the Netherlands, and the UK. Eligible patients were aged 18 years or older, had a diagnosis of chronic plaque psoriasis for at least 6 months before baseline, had currently moderate to severe disease, and were methotrexate treatment-naive. Participants were randomly assigned (3:1), via a computer-generated random number sequence integrated into an electronic data capture system, to receive either methotrexate at a starting dose of 17·5 mg/week or placebo for the first 16 weeks, followed by methotrexate treatment of all patients up to 52 weeks (methotrexate–methotrexate vs placebo–methotrexate groups). Dose escalation to 22·5 mg/week was allowed after 8 weeks of methotrexate treatment if patients had not achieved at least a 50% reduction in baseline Psoriasis Area and Severity Index score (PASI), with corresponding volume increases in placebo injections. Treatment was combined with folic acid 5 mg/week. Group allocation was concealed from participants and investigators from the time of randomisation until an interim database lock at week 16, and was open label from week 16 onwards, with no masking of participants or investigators. The primary efficacy endpoint was a 75% reduction in PASI score (PASI 75) from baseline to week 16. We did analysis by modified intention to treat, with non-responder imputation. This study is registered with EudraCT, number 2012-002716-10. Findings: Between Feb 22, 2013, and May 13, 2015, we randomly assigned 120 patients to receive methotrexate (n=91) or placebo (n=29). At week 16, a PASI 75 response was achieved in 37 (41%) patients in the methotrexate group compared with three (10%) patients in the placebo group (relative risk 3·93, 95% CI 1·31–11·81; p=0·0026). Subcutaneous methotrexate was generally well tolerated; no patients died or had serious infections, malignancies, or major adverse cardiovascular events. Serious adverse events were recorded in three (3%) patients who received methotrexate for the full 52 week treatment period. Interpretation: Our findings show a favourable 52 week risk–benefit profile of subcutaneous methotrexate in patients with psoriasis. The route of administration and the intensified dosing schedule should be considered when methotrexate is used in this patient group. Funding: Medac.